Enhancing Student's Reading Comprehension through Ai Based Learning Media Ready Ai' For Grade High School - Fikroh gani, Liyundzira; Ismahani , Siti (International Journal of English and Applied Linguistics (IJEAL), 2025)
The purpose of this study is to see the effect of Read-IA digital media significantly affecting mastery in reading comprehension in students. The population of this study were high school students in grade XI in Medan city and 20 students from three different classes with a total number of 26 people in one class who used the Read-AI platform were taken as samples using purposive sampling technique, which is the selection of samples based on certain criteria that are relevant to the research objectives. The sample criteria were the XI grade students who had used the Read-AI platform actively in learning activities for at least two learning meetings. Data were collected through an initial test and a final test to measure the improvement of learning outcomes and reading comprehension, as well as a structured questionnaire. Data analysis was conducted using SPSS application, with paired sample t-test technique, descriptive statistics, reliability test (Cronbach's Alpha), and correlation between items. The results showed a significant increase in students' reading comprehension scores, with an average increase of 20% (p < 0.05). These findings demonstrate that AI-based adaptive technology can have a positive impact on reading instruction at the secondary level. Nevertheless, digital infrastructure limitations and the need for teacher training remain major challenges. This study contributes meaningfully to the development of modern literacy strategies that are contextual, innovative, and data-driven.